Striatal Dopamine Deficit and Motor Impairment in Idiopathic Normal Pressure Hydrocephalus - Pozzi, Nicoló Gabriele; Brumberg, Joachim; Todisco, Massimiliano; Minafra, Brigida; Zangaglia, Roberta; Bossert, Irene; Trifirò, Giuseppe; Ceravolo, Roberto; Vitali, Paolo; Isaias, Ioannis Ugo; Fasano, Alfonso; Pacchetti, Claudio (Movement disorders, 2021)
ABSTRACT Background Idiopathic normal pressure hydrocephalus can present with parkinsonism. However, abnormalities of the striatal dopamine reuptake transporter are unclear. Objectives To explore presence and features of striatal dopaminergic deficit in subjects with idiopathic normal pressure hydrocephalus as compared to Parkinson's disease (PD) patients and healthy controls. Methods We investigated 50 subjects with idiopathic normal pressure hydrocephalus, 25 with PD, and 40 healthy controls. All participants underwent [123I]‐N‐ω‐fluoropropyl‐2β‐carbomethoxy‐3β‐(4‐iodophenyl)nortropane and single‐photon emission computed tomography to quantify the striatal dopamine reuptake transporter binding. All subjects with idiopathic normal pressure hydrocephalus underwent a levodopa (l‐dopa) challenge test and magnetic resonance imaging to evaluate ventriculomegaly and white matter changes. Gait, cognition, balance, and continence were assessed with the Idiopathic Normal Pressure Hydrocephalus Rating Scale, and parkinsonism with the motor section of the Movement Disorder Society‐Unified Parkinson's Disease Rating Scale. All patients completed a 2‐year follow‐up. Results A total of 62% of patients with idiopathic normal pressure hydrocephalus featured a reduced striatal dopamine reuptake transporter binding, which correlated with the severity of parkinsonism but not with features of ventriculomegaly or white matter changes. Unlike PD, this dopaminergic deficit in idiopathic normal pressure hydrocephalus was more symmetric and prominent in the caudate nucleus. Conclusions Subjects with idiopathic normal pressure hydrocephalus can present a reduction of striatal dopamine reuptake transporter binding, which is consistent with the severity of parkinsonism and qualitatively differs from that found in PD patients. Longitudinal interventional studies are needed to prove a role for striatal dopamine reuptake transporter deficit in the pathophysiology of idiopathic normal pressure hydrocephalus. © 2020 International Parkinson and Movement Disorder Society